Electrochemically controlled dearomative 2, 3-difunctionalization of indoles to synthesize oxoindoline derivatives. Issue 14 (14th June 2022) - Peng, Xichao; Wen, Linzi; Ning, Zuozhou; Zhang, Zhicheng; Sun, Chengbo; Tang, Yu; Feng, Pengju
Abstract : Electrochemistry-controlled dearomative 2, 3-difunctionalization of indoles via electrochemically anode-selective oxidative cross coupling was achieved, allowing tunable access to a wide variety of synthetically useful oxindole derivatives. Abstract : A general and practical protocol for an electrochemically controlled dearomative 2, 3-difunctionalization of indoles via electrochemical anode-selective oxidative cross-coupling has been demonstrated. The reaction runs under metal-, oxidant- and catalyst-free conditions, allowing tunable access to a wide variety of synthetically useful oxindole derivatives, such as 3, 3-diaryl-2-oxindole, 3-hydroxy-2-oxindole and 2-hydroxy-3-oxindole derivatives. Finally, a preliminary mechanistic study indicated that the indole radical cation could undergo two different pathways via switching the anode materials under the same reaction conditions to deliver various products.